웹기반 전통흙건축재료 정보서비스 설계 및 구현 - 이상돈(Sangdon Lee) (한국콘텐츠학회 논문지, 9(1), 2009)
This paper describes design and implementation of a Web-based information service that supports management and retrieval of use cases for earth-related materials in traditional Korean construction process. Managed data are gathered from old traditional books which are written in Chinese characters. Development needs to consider providing users effective interface to retrieve information from the service easily. Gathering and analysis of earth-related data are processed in parallel to the database construction. Data store and management needs to be flexible enough. This paper introduces several design and implementation issues for the developed service, and proposes solutions for the them. 본 논문에서는 전통 건축을 위해 사용되었던 흙건축 재료와 관련된 정보를 웹 환경에서 관리하고 검색할 수 있도록 하기 위한 웹 기반 정보서비스의 설계 및 개발에 대하여 기술한다. 전통흙건축재료 정보서비스는 특히 고문헌 자료를 바탕으로 하므로, 일반 사용자가 이해하기 어려운 전문 한자 용어 중심의 데이터를 기반으로 정보 검색이 수행되는 불편을 최소화시킬 수 있는 방안이 요구된다. 또한 자료 수집 및 분석이 데이터베이스 구축과 병행되므로 데이터의 확장성에 대한 고려가 필요하기도 하다. 본 논문에서는 전통흙 건축재료를 위한 정보서비스의 설계 및 개발 과정에서 주요 이슈들을 도출하고 이를 해결하는 여러 방안들을 제시한다.